Graphite as A Hydrogen Storage in Fuel Cell System: Computational Material Study for Renewable Energy - Gunawan, Rahmat; Radiman, Cynthia Linaya; Martoprawiro, Muhamad Abdulkadir; Dipojono, Hermawan K. (Jurnal ILMU DASAR, 2016)
The Hydrogen storage based-graphite materials have been investigated theoretically via Density Functional Theory (DFT) approach. The native graphite was compared to the modified graphite, namely the intercalation graphite (GICs, graphite intercalated compounds). Here the GICs was intercalated by alkali metals (Li, Na and K). The electronic structures, energetics and atomic orbital contributions of hydrogen-graphite system, GICs, and hydrogen-GICs were studied by calculation approach of gradient corrected PBE (Perdew-Burke-Ernzerhof) for recovery of exchange-correlation energy. The calculation was supported by using basis set of the plane waves whereas the computation of electron-core by using Ultrasoft Vanderbilt pseudopotential. The computational calculation provides four main studies i.e. molecular geometry relaxation, determination of electronic bands structure of energy, energy state density (DOS) and atomic orbital contribution by charge density differences.Keywords: Density Functional Theory, hydrogen gas, graphite intercalated material